Genome-wide identification, characterization and phylogenetic analysis of 50 catfish ATP-binding cassette (ABC) transporter genes. - Shikai Liu; Qi Li; Zhanjiang Liu (PLoS ONE, 2013)
Although a large set of full-length transcripts was recently assembled in catfish, annotation of large gene families, especially those with duplications, is still a great challenge. Most often, complexities in annotation cause mis-identification and thereby much confusion in the scientific literature. As such, detailed phylogenetic analysis and/or orthology analysis are required for annotation of genes involved in gene families. The ATP-binding cassette (ABC) transporter gene superfamily is a large gene family that encodes membrane proteins that transport a diverse set of substrates across membranes, playing important roles in protecting organisms from diverse environment.In this work, we identified a set of 50 ABC transporters in catfish genome. Phylogenetic analysis allowed their identification and annotation into seven subfamilies, including 9 ABCA genes, 12 ABCB genes, 12 ABCC genes, 5 ABCD genes, 2 ABCE genes, 4 ABCF genes and 6 ABCG genes. Most ABC transporters are conserved among vertebrates, though cases of recent gene duplications and gene losses do exist. Gene duplications in catfish were found for ABCA1, ABCB3, ABCB6, ABCC5, ABCD3, ABCE1, ABCF2 and ABCG2.The whole set of catfish ABC transporters provide the essential genomic resources for future biochemical, toxicological and physiological studies of ABC drug efflux transporters. The establishment of orthologies should allow functional inferences with the information from model species, though the function of lineage-specific genes can be distinct because of specific living environment with different selection pressure.